English Language Learning from the Perspective of Students - Pre-service Preschool Teachers - Radmila D. Palinkašević (University of Belgrade, Teacher Education Faculty, 2021)
Starting from the hypothesis that an identification and a more detailed study of students' conceptual sphere regarding learning English language will result in mapping the fields in the tertiary-level teaching of English as a foreign language that need improvement, in the academic year 2018/19 we conducted a survey among all undergraduate students at the Preschool Teacher Training College "Mihajlo Palov" in Vršac. A total of 125 respondents filled out an anonymous questionnaire designed to reveal the source domains through which pre-service preschool teachers perceive learning English as a foreign language. A qualitative analysis of the researched corpus made it possible to single out five dominant conceptual metaphors of different source domains for the concept of English language learning. Among the obtained metaphors, special attention was given to selecting the metaphors with a methodological potential for implementation in teaching, as well as to the suggestions for modelling the so-called disruptive metaphors that have a negative effect on the English language acquisition.